Relationship of mast cell density with lymphangiogenesis and prognostic parameters in breast carcinoma. Issue 4 (13th March 2017) - Keser, Sevinc H.; Kandemir, Nilufer O.; Ece, Dilek; Gecmen, Gonca G.; Gul, Aylin E.; Barisik, Nagehan O.; Sensu, Sibel; Buyukuysal, Cagatay; Barut, Figen
Abstract: In many cancers, mast cell density (MCD) in the tumor microenvironment is associated with tumor progression and, to a greater extent, angiogenesis. Our study was designed to investigate the correlation between MCD, tumor lymphangiogenesis, and several well‐established prognostic parameters in breast cancer. One hundred and four cases of invasive breast carcinoma diagnosed in our clinic between 2007 and 2011 were included. Mast cells and lymphatic vessels were stained with toluidine blue and D2‐40, respectively, and their densities were calculated in various areas of tumors and lymph nodes. The variables of MCD and lymphatic vessel density (LVD) were compared using prognostic parameters as well as with each other. As tumor size and volume increased, MCD increased comparably in metastatic lymph nodes; intratumoral and peritumoral LVD also increased. Lymphovascular invasion, lymphatic invasion, perineural invasion, and estrogen receptor positivity were positively related to intratumoral MCD. The relationship between peritumoral MCD and nontumoral breast tissue MCD was statistically significant. Stage was correlated with MCD in metastatic lymph nodes. Metastatic lymph node MCD and intratumoral MCD were also significantly related. Stage, lymphatic invasion, perineural invasion, lymphovascular invasion, and metastatic lymph node MCD were all correlated with intratumoral and/or peritumoral LVD. As nuclear grade increased, intratumoral LVD became higher. In breast carcinoma, MCD, depending on its location, was related to several prognostic parameters. Notably, mast cells may have at least some effect on lymphangiogenesis, which appears to be a predictor of tumor progression.